The Impact of Neighbour, Colleague, and Family Peers on Parental Labour Supply - Jordy Meekes; Max van Lent (Institute of Labor Economics (IZA), 2025)
Child penalties in paid working hours are persistent and widen the gender earnings gap. This paper studies an important mechanism through which working hours are affected: peer effects. Using three unique layers of peer networks: neighbours, colleagues, and family, we analyse peer effects on individuals' paid working hours. We analyse peer effects up to six years after childbirth on individuals who become first-time parents in the period 2014-2018, using Dutch full-population administrative monthly microdata up to September 2024. The identification strategy exploits exogenous variation in peers' working hours through peers-of-peers. Our research is the first to establish long-term statistically significant peer effects on fathers' working hours. The results indicate positive peer effects on fathers and mothers, where colleague peers are more important than neighbour peers and family peers.
Keywords: J22; D85; C26; 330; family peers; neighbour peers; colleague peers; paid working hours; peers-of-peers